Halal Tourism Opportunities And Challenges In East Java - Otto Andri Priyono (Ulumuna: Jurnal Studi Keilsman, 2018)
The Ministry of Tourism has made East Java province a national halal tourism development area. This is supported by the existence of various religious tourism objects, natural and artificial tourism objects, organizing annual cultural events and adequate infrastructure. The purpose of this study is to review the potential and formulate halal tourism development strategies in East Java. This study uses secondary data with qualitative methods and SWOT analysis techniques. Internal analysis shows the strengths and weaknesses as well as external analysis shows the opportunities and challenges of weakness in the development of halal tourism in East Java. Strength factors include the diversity of tourist destinations, infrastructure supporting tourist mobility, and the level of tourist visits. Weakness factors include promotion and branding, experts who are experts and means of supporting halal tourism. Opportunity factors include the support of government policies, the existence of supporting institutions, the international reputation of Indonesian halal tourism. Threat factors include economic stability, security stability and competition for the halal tourism industry. Based on the analysis of internal and external factors, the formulation of halal tourism development strategies in East Java include: a) S-O strategy: encouraging domestic and foreign investment in halal tourism development in East Java; b) W-O strategy: development of East Java halal tourism multiplatform information based on IoT; c) S-T strategy: build a halal pariwistaa halal in East Java entitled "Khazanah East Java"; d) W-T strategy: Establishment of a Special Economic Zone for Halal Tourism which is supported by the establishment of an institution of the Halal Tourism Management Authority of East Java Province Keywords: Halal Tourism, Opportunities, Challenges, East Java